(untitled) (Revista Contexto & Educação, 2023)
This is a research on the literacy process of children in the first three years of elementary school (Initial Literacy Cycle). The main objective of the research was to understand and analyze how this process is carried out, taking into account the narratives of literacy teachers about their experiences in school life. As a methodological procedure, we used the qualitative approach, with the technique of participant observation and semi-structured interview. For the research, a state school located in the municipality of Carangola / MG was selected, with the participation of three literacy teachers. As a result, we point out that the teaching experiences define the way teachers develop the teaching-learning process, the influence of pedagogical trends, literacy methods, the literacy environment and other elements relevant to the development and learning of children. Keywords: Literacy; search; literacy teachers.